Dietary intake of mixture coarse cereals prevents obesity by altering the gut microbiota in high-fat diet fed mice. (January 2021) - Ji, Yang; Ma, Ning; Zhang, Junmiao; Wang, Hetong; Tao, Tianyi; Pei, Fei; Hu, Qiuhui
Abstract: Functional components including β-glucan, dietary fiber, resistant starch and polyphenols extracted from various coarse cereals have been reported to prevent high-fat diet (HFD) induced obesity via modulating gut microbiota. In this study, millet, maize, oat, soybean, and purple potato were ultrafine comminuted, mixed, and then extruded for the preparation of puffed mixture coarse cereals. HFD was used to investigate the effects of mixture coarse cereals on obesity and gut microbiota in mice. The results showed that dietary intake of mixture coarse cereals could decrease body weight gain and fat accumulation, improve the blood glucose tolerance and serum lipids levels, reduce the systemic inflammation, and down-regulate the expression of hepatic lipogenic genes. In addition, the levels of SCFAs and the composition of gut microbiota were investigated. The results indicated that mixture coarse cereals could promote the release of SCFAs, enhance the diversity of gut microbiota, and increase the relative abundance of Lactobacillus and Bifidobacterium, which might contribute to the anti-obesity activity. Present work suggested that the mixture coarse cereals could be developed as a nutraceutical for the prevention of HFD-induced obesity. Graphical abstract: Image 1 Highlights: Millet, maize, oat, soybean and purple potato were extruded for the puffed powders. Dietary intake of mixture coarse cereals prevented HFD-induced obesity in mice. Mixture coarse cereals promoted the release of SCFAs. Mixture coarse cereals enhanced the relative abundance of Lactobacillus and Bifidobacterium.